Determinants of Islamic Banks' Profitability in an Emerging Economy: An Empirical Evidence from Bangladesh - Hossain, Mohammad Azhar (Finance & Economics Review, 2024)
Purpose: This study investigates the factors influencing the profitability of Sharia-based Islamic banks operating in Bangladesh. Methods: Using panel data from 2017 to 2023, the current analysis shows how factors particular to individual banks have impacted the profitability of Bangladeshi banks. To complete this analysis, only Islamic banks are taken into consideration. In this paper, the factors that affect Bangladesh's Islamic banking industry's profitability are clarified. 10 Islamic banks operating in Bangladesh are included in the sample. The study investigates internal factors such as size, liquidity risk, operational effectiveness, credit risk, financial risk, and capital adequacy. The analysis is conducted using panel data regression with fixed effect. Results: The result shows that operating efficiency, financial risk, and liquidity risk are the most relevant bank-specific characteristics in determining the Islamic banks’ profitability in Bangladesh. Implications: The study suggests that bankers should keep a close observation of credit and liquidity risk indicators, diversify their revenue streams, and minimize expenses. Moreover from the regulatory perspective, the performance of the banks should be evaluated based on their operational efficiency and ability to generate profit. The policy direction will be directed towards enhancing resilience by reducing the risk internally and increasing the efficiency of the Islamic banks to intensify the robustness and stability of this sector. Originality: While numerous previous studies have provided various explanations of the factors influencing bank profitability, this research specifically examines the internal factors affecting the profitability of Islamic Banks in Bangladesh, an emerging market.